Catamenial pneumothorax. Issue 12 (25th November 2008) - Simpson, A; Skelly, E
Abstract : Pneumothorax is a potentially life-threatening condition caused by an accumulation of air or gas in the pleural space. This may occur either spontaneously or as a result of disease or injury. The term "catamenial" is derived from the Greek meaning "monthly". Catamenial pneumothorax is a rare complication of endometriosis. A patient with a history of endometriosis presented to the accident and emergency department with increased abdominal pain, shortness of breath and wheeze. She was subsequently found to have a right-sided pneumothorax which was initially aspirated. However, the pneumothorax recurred and required chest drain insertion and admission to a medical ward. Further recovery was uneventful. It is important to maintain a high index of suspicion of catamenial pneumothorax in patients with a history of endometriosis.